2013
DOI: 10.1007/s00381-012-2012-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of propranolol for management of pain in children with vertebral hemangioma: report of two cases

Abstract: Propranolol is a beta blocker which is safely used in the management of infantile hemangiomas. This is the first report demonstrating its efficacy in symptomatic treatment of childhood VH. The lesions did not show any regression, but the pain relief obtained was very significant under propranolol therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…[5] In the fourth case (e.g., 4th study), Uzunaslan et al described using propranolol to treat T5 aggressive hemangioma. [6] Patient 8 years of age, without epidural invasion, improved within 2 months. On repeat magnetic resonance imaging scan, 18 months later, the lesion did not decrease in size [6] [Table 2].…”
Section: Four Patients Evaluated With Aggressive Hemangiomasmentioning
confidence: 94%
See 3 more Smart Citations
“…[5] In the fourth case (e.g., 4th study), Uzunaslan et al described using propranolol to treat T5 aggressive hemangioma. [6] Patient 8 years of age, without epidural invasion, improved within 2 months. On repeat magnetic resonance imaging scan, 18 months later, the lesion did not decrease in size [6] [Table 2].…”
Section: Four Patients Evaluated With Aggressive Hemangiomasmentioning
confidence: 94%
“…[6] Patient 8 years of age, without epidural invasion, improved within 2 months. On repeat magnetic resonance imaging scan, 18 months later, the lesion did not decrease in size [6] [Table 2].…”
Section: Four Patients Evaluated With Aggressive Hemangiomasmentioning
confidence: 94%
See 2 more Smart Citations
“…Currently, this condition is treated by oral administration of PPN, causing side effects (Padula, Nicoli, Pescina, & Santi, 2019). Recently, some studies have shown the potent effect of PPN as a local anesthetic, similar to lidocaine, which suggests the possible exploration of this drug for local skin delivery (Chen, Chiu, Wei, Hung, & Wang, 2015; Uzunaslan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%